2011
DOI: 10.1002/aenm.201100046
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hole Transport Material Pore Filling on Photovoltaic Performance in Solid‐State Dye‐Sensitized Solar Cells

Abstract: A detailed investigation of the effect of hole transport material (HTM) pore filling on the photovoltaic performance of solid‐state dye‐sensitized solar cells (ss‐DSCs) and the specific mechanisms involved is reported. It is demonstrated that the efficiency and photovoltaic characteristics of ss‐DSCs improve with the pore filling fraction (PFF) of the HTM, 2,2’,7,7’‐tetrakis‐(N, N ‐di‐ p ‐methoxyphenylamine)9,9’‐spirobifluorene(spiro‐OMeTAD). The mechanisms through which the improvement of photovoltaic charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
104
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(110 citation statements)
references
References 47 publications
5
104
0
Order By: Relevance
“…16 Some studies have already argued that hole transport between dyes could happen in solid state devices and plays a role towards improved dye regeneration. 17,8,18,19,20,9 However, to our knowledge, no experimental evidence for this has been reported to date.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…16 Some studies have already argued that hole transport between dyes could happen in solid state devices and plays a role towards improved dye regeneration. 17,8,18,19,20,9 However, to our knowledge, no experimental evidence for this has been reported to date.…”
Section: Introductionmentioning
confidence: 62%
“…5,6,7,8,9 Some of these studies have shown that, under optimized conditions and for different dyes and thickness of the TiO2 layer, the dye regeneration yield of the device ranges between 0.9 and 1. This result suggests that either almost complete coverage of the dyed surface is achievable or transfer of holes between the dye molecules enables improved charge collection from dyes that are uncovered by the HTM.…”
Section: Introductionmentioning
confidence: 99%
“…All cells made from higher spiro-concentrations have similar electron lifetimes, with overlapping points at all studied bias light intensities. These results are in good agreement with a study by Melas-Kyriazi et al, where improved pore-filling was found to extend the electron lifetime at short circuit to around 10 ms. 41 While the electron lifetime increases for high pore-filling fractions, no trend was observed in the extraction lifetimes at high light bias, as shown in Figure 6b, where most measurement points overlap.…”
Section: Solid-state Dye-sensitized Solar Cellsmentioning
confidence: 79%
“…The hydrophobic dinonyl aliphatic moiety of Z907 allows for a better wetting of the dye-sensitized surface by the organic HTM and the formation of a more conformal heterojunction. 34 Hence, its use is preferred to that of N719 dye in the fabrication of efficient solid-state DSSCs. Upon pulsed laser excitation, solid-state samples displayed a steep rise of transient absorption observed at short times, corresponding to the appearance of the oxidized state of the dye produced by ultrafast electron injection ( Figure 4A).…”
mentioning
confidence: 99%